DEVELOPMENT OF PROBLEM BASED LEARNING MODULES IN THE STUDENT LEARNING - Ramalia, Hadijah (Universitas Negeri Medan, 2024)
This study aims to determine the physics concept contained in the traditional toy othok-othok ship. This research was conducted using interview techniques. Data were collected at Untung Suropati Street, Kalipancur, Ngaliyan, Semarang. The data that has been obtained are then analyzed to find out what are the physics concepts contained in the othok-othok ship toy. The results showed that the othok-othok toy contained the physics concepts of Archimedes' Principles, First and Second Laws of Thermodynamics, Newton's Third Law, and sound. Keywords: physics concept, othok-othok shipThis study aims to determine the physics concept contained in the traditional toy othok-othok ship. This research was conducted using interview techniques. Data were collected at Untung Suropati Street, Kalipancur, Ngaliyan, Semarang. The data that has been obtained are then analyzed to find out what are the physics concepts contained in the othok-othok ship toy. The results showed that the othok-othok toy contained the physics concepts of Archimedes' Principles, First and Second Laws of Thermodynamics, Newton's Third Law, and sound. Keywords: physics concept, othok-othok ship